2013
DOI: 10.1017/jfm.2012.627
|View full text |Cite
|
Sign up to set email alerts
|

A simple constitutive model for predicting the pressure histories developed behind rigid porous media impinged by shock waves

Abstract: Shock wave attenuation by means of rigid porous media is often applied when protective structures are dealt with. The passage of a shock wave through a layer of porous medium is accompanied by diffractions and viscous effects that attenuate and weaken the transmitted shock, thus reducing the load that develops on the target wall that is placed behind the protective layer. In the present study, the parameters governing the pressure build-up on the target wall are experimentally investigated using a shock tube f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…In the past, the same shock tube facility was fitted with a long driver in order to generate a step function loading, which is more typical for conventional shock tubes. The results from this earlier study were used to formulate the RS model (Ram & Sadot 2013). Some of these results are also used in the present study to demonstrate some of the new points that are raised in the discussion section.…”
Section: Short Driver Shock Tubementioning
confidence: 86%
See 4 more Smart Citations
“…In the past, the same shock tube facility was fitted with a long driver in order to generate a step function loading, which is more typical for conventional shock tubes. The results from this earlier study were used to formulate the RS model (Ram & Sadot 2013). Some of these results are also used in the present study to demonstrate some of the new points that are raised in the discussion section.…”
Section: Short Driver Shock Tubementioning
confidence: 86%
“…As a result, the pressure buildup profile could be predicted for a given incident shock wave and standoff distance. Ram & Sadot (2013) also showed that this model could be used to predict the pressure buildup using a variety of porous-like barriers such as a series of grids or perforated plates. While the RS model predicts very well the pressure buildup as a result of the impingement of constant-velocity shock waves (step jump) on the front face of porous samples, its validity is yet to be checked against other imposed pressure profiles such as the one that results from the impingement of blast waves (close to exponentially decaying).…”
Section: Analytical Modellingmentioning
confidence: 98%
See 3 more Smart Citations